2014
DOI: 10.1002/ajim.22352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a community‐based participatory farmworker eye health intervention in the “black dirt” region of New York State

Abstract: The intervention was effective in significantly reducing eye pain, and to a lesser extent, redness. Future eyewear promotion programs should offer a range of eye wear, tailor offerings to local climate and tasks, evaluate eyewear durability, and include eye drops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Many studies comment on the inherently limited nature of self‐reported results when working with MSFWs. However, these limitations have been largely attributed to recall bias [Quandt et al, ; Salvatore et al, ; Earle‐Richardson et al, ; Kearney et al, ]. While recall bias is certainly a possibility for farmworkers who were asked to report how many hours they wore the kneepads, we posit that it was not the only biasing factor at play in our study.…”
Section: Discussionmentioning
confidence: 85%
“…Many studies comment on the inherently limited nature of self‐reported results when working with MSFWs. However, these limitations have been largely attributed to recall bias [Quandt et al, ; Salvatore et al, ; Earle‐Richardson et al, ; Kearney et al, ]. While recall bias is certainly a possibility for farmworkers who were asked to report how many hours they wore the kneepads, we posit that it was not the only biasing factor at play in our study.…”
Section: Discussionmentioning
confidence: 85%
“…Earle-Richardson and colleagues employed CBPR to decrease eye irritation among migrant farm workers[30]. This was the only research that created sustainable results and one of three to demonstrate long-term commitment to a community.…”
Section: Resultsmentioning
confidence: 99%
“…It not only requires community involvement from the development of a research question, it also requires participation throughout the entire process, usually stemming from a longstanding relationship between the two entities[50]. Both CBPR projects detailed in this review, the Photovoice project[29] and the project that improved the eye health of migrant farm workers[30], involved community members from the study design through implementation. CBPR approaches may enhance community capacity to address health inequities [54].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, poor visibility, discomfort, and hot weather discouraged workers from using PPE in our setting. Offering workers PPE that is tailored to the local climate and tasks, including anti-fog coating, might enhance its usage (Ademola-Popoola et al 2005 ; Crebolder and Sloan 2004 ; Earle-Richardson et al 2014 ). Furthermore, apprenticeship training was negatively associated with the usage of face shields and welding helmets in our study.…”
Section: Discussionmentioning
confidence: 99%